Minimal residual disease (MRD) detection in acute lymphoblastic leukaemia based on fusion genes and genomic deletions: towards MRD for all. (1st August 2021) - Kuiper, Roland P.; Hoogeveen, Patricia G.; Bladergroen, Reno; van Dijk, Freerk; Sonneveld, Edwin; van Leeuwen, Frank N.; Boer, Judith; Sergeeva, Irina; Feitsma, Harma; den Boer, Monique L.; van der Velden, Vincent H. J.
Summary: Minimal residual disease (MRD) diagnostics are implemented in most clinical protocols for patients with acute lymphoblastic leukaemia (ALL) and are mostly performed using rearranged immunoglobulin (IG) and/or T‐cell receptor (TR) gene rearrangements as molecular polymerase chain reaction targets. Unfortunately, in 5–10% of patients no or no sensitive IG/TR targets are available, and patients therefore cannot be stratified appropriately. In the present study, we used fusion genes and genomic deletions as alternative MRD targets in these patients, which retrospectively revealed appropriate MDR stratification in 79% of patients with no (sensitive) IG/TR target, and a different risk group stratification in more than half of the cases.